Supply of and demand for agricultural extension services in Malawi – A synthesis - Ragasa, Catherine (International Food Policy Research Institute, 2018)
There are more than 120 organizations and programs in Malawi working on agriculture that include extension service provision among their main activities. However, extension service provision is largely "projectized," uncoordinated, and unmonitored. This Note synthesizes the main findings from the recent surveys and interviews of households, communities, and service providers about the status of access to these extension services, challenges on both demand and supply sides, and suggestions and reflections that can inform the ongoing development of the National Agricultural Extension Strategy.